A study of shoulder and hip rotation in short-distance front crawl swimming - Hyodo, H.; Koga, D.; Wada, T.; Sengoku, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2021)
In this study, we investigated the rotation motion of the trunk during sprint front crawl swimming. The shoulder and hip rotation movements at different swimming velocities were compared and analyzed. Ten male swimmers specializing in front crawl sprinting participated. Two 10-second trials of front crawl without breathing were conducted. One employed the average swimming velocity for a 50-m race and the other that for a 100-m race. For swimming motion assessment, actual coordinate values were collected by three-dimensional motion analysis. The stroke frequency (SF), shoulder and hip rotation angle (ShR, HiR), and the time until ShR and HiR became maximal in the pull phase were calculated. As a result, in the 50-m race average trial, the value of ShR was significantly smaller than that in the 100-m race average trial. In addition, the time to reach the maximum value of HiR was significantly shorter in the 50-m race average trial. Therefore, it is probable that the timing of shoulder and hip rotation movements will differ between the 50-m and 100-m races as a result of the change in the time to reach the ShR and HiR peaks, since the average swimming velocity in the 50-m front crawl is higher than that in the 100-m front crawl.